Strategi pemasaran cemilan produk keripik pisang melalui media online instagram - Rahsel, Yoeyong; Gumanti, Miswan (ARKA INSTITUTE, 2022)
The use of social media as an effective marketing strategy for all businesses, from food, snacks, clothing, banking and other services. The use of social media is based on the rapid growth of the millennial generation where its use is very common for anyone. Marketing strategies through social media such as Instagram are very familiar to the millennial generation. Instagram is a real example of making marketing more interesting, better and more practical. Banana chip products also don't want to be left behind in utilizing Instagram social media. The purpose of this study was to determine the marketing strategies carried out by shops in Bandar Lampung. The research method used was qualitative research using a marketing mix. The results of the study showed positive results in the use of Instagram for marketing their products. It can be concluded that the use of marketing strategies using Instagram is more beneficial than using other conventional methods.